Handling and management of hydric recharge zones in micro watersheds and water sources for human consumption in Honduras - Rodas Velásquez, G.R. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),2008